IN-HOUSE INSTITUTIONS AS A CORPORATE MANAGEMENT TOOL - M. V. Kramin (Russian Journal of Economics and Law)
The work gives the social-economic characteristic of in-house institutions connected with innovations management and human capital of a corporation.